Otoritas Keagamaan Nyai Pandalungan - Fazlul Rahman (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
This research discusses the dynamic phenomenon of the religious authority of the kiai’s wives, who usually known as “nyai”, in the area of Pandalungan, East Java, Indonesia. More specifically, this study highlights the problem of the subordination of nyai’s religious authority, or of female ulama’s in general, in the pesantren world. The fact that the glory of a pesantren is often only attributed to the leadership skills and greatness of the individual charisma of a kiai, the role of a nyai is, at this point, more often be subordinated or considered as the second actor behind the greatness of the husband's name. This problem is increasingly complex when it is faced with local cultural realities which significantly contribute to down-grading the existence of female ulama. Based on the existing theories in gender discourse, religious authority in Islam, and female psychology, this study concludes that the religious authority of women in Islam in Pandalungan is actually dynamic. Local cultural factors that are inherited from generation to generation and the psychology of a woman, in this case, become the main factor behind the gap of male and female religious authority in pesantren and of ideal-theological view of women and local culture realities in general.